Independent Animal Feed Processing To Improve The Economy Of The Community In Simpang Village, Pasaman, West Sumatra - Syukri, Daimon; Salim, Emil; Rahma Yanti, Nika; Tifani Puari, Aninda (Andalasian International Journal of Social and Entrepreneurial Development, 2021)
Background: The absence of a corn processing machine is one of the problems experienced by Aur Serumpun farmer groups at Nagari Simpang. Methodology: The team of community services from Andalas University handed over a corn grinder that can be used to process dry corn into animal feed. The corn milling machine delivered is an electric machine with a small capacity that can be used for small-scale production. Conclusion: Members of the farming group have expressed their gratitude for the procedure of transferring the grinder. The existence of this tool benefits the community significantly because it allows them to make their own feed and sell it to other villages at a lesser cost.